PENINGKATAN TINGKAT HUNIAN MELALUI MANAJEMEN HOMESTAY BERBASIS WEBSITE DI KOTA PAYAKUMBUH - Asniati Bahari; Elvira Luthan; Yurniwati Yurniwati; Jonhar Jonhar; Warnida Warnida; Riza Reni Yanti; Ihsani Mazelfi; Ali Nursal (Jurnal Hilirisasi IPTEKS, 2023)
Currently, homestays in the city of Payakumbuh generally do not maximize the use of information systems. This is due to a lack of understanding among homestay owners about appropriate governance methods and a shortage of knowledge regarding computer-based information system management and homestay operation capabilities. The objective of this activity is to implement a homestay management information system in the city of Payakumbuh. The method employed for this activity is training. A total of 23 homestay owners in Payakumbuh participated in the training. This initiative aims to implement a website-based information system to enhance homestay owners' understanding of effective governance, computer-based information system management, and operational capabilities in managing homestay systems. The outcomes of this initiative include improved capabilities among homestay owners to effectively utilize the Website-Based Homestay Management Information System. This training not only benefits homestay owners but also faculty, departments, and the university. It creates opportunities for homestay managers to collaborate and share experiences, thereby strengthening the SME community in the homestay sector in Payakumbuh. The implementation of a website-based information system in homestay management is intended to expand promotional networks, catering not only to local tourists but also to international visitors. In conclusion, this training program has significantly benefited homestay managers and has the potential to support local economic growth and the development of the tourism sector in the Payakumbuh region. It is anticipated that this initiative will contribute knowledge towards homestay management development and the application of information technology in the tourism sector.